ANALISIS KEBIJAKAN PAJAK TERKAIT KEWAJIBAN BANKMELAPORKAN DATA TRANSAKSI PENGGUNAAN KARTU KREDIT NASABAH KE DIREKTORAT JENDERAL PAJAK MENURUT PERATURAN MENTERI KEUANGAN NOMOR 39/PMK.03/2016 - Selvi Selvi; Sennytia Sennytia (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2017)
This research aims to determine the legal basis and the development of bank secrecy regulations in Indonesia related to taxation, as well as to determine the policy of the Minister of Finance Regulation No. 39 / PMK.03 / 2016 related to the reporting of data transactions using credit cards to the Directorate General of Taxation. The research method used is qualitative method, which method is more suitable for use when discussing social issues in general. The data collected is not in the form of figures, but data derived from interviews and other official documents. The results of the study explained that the basic legal and regulatory developments of bank secrecy in Indonesia related to taxation regulated Law No. 10 of 1998 Article 41 paragraph (1), Law on General Provisions and Tax Procedures (CTP) of Article 35 paragraph (1) , Minister of Finance Regulation No. 87 / PMK.03 / 2013 on Procedures Demand description or evidence of the parties bound by the Confidentiality Obligations, and Bank Indonesia Regulation Number 2/19 / PBI / 2000 on Procedures for Granting Permission command or Written Opens Bank secrecy. Bank Secrecy also has exceptions including for tax purposes as set out in Finance Minister Regulation No. 39 / PMK.03 / 2016 regarding the liabilities of the bank in the reporting of data transactions using credit cards to the Directorate General of Taxation. Through research conducted suggested the existence of clear legal provision that the tax inspector will not experience bottlenecks in the process of examination of taxpayer data and the policy is expected to be coordinated in advance by the parties are related because in running this policy required accurate data good data from the banks as well as taxation and there must be a commitment that the data will be open for tax purposes guaranteed confidentiality.